Optimized N application improves N absorption, population dynamics, and ear fruiting traits of wheat - Zhang, Xiangqian; Xu, Yunji; Du, Shizhou; Qiao, Yuqiang; Cao, Chengfu; Chen, Huan (Frontiers in Plant Science, 2023)
Optimizing N application amount and topdressing ratio can increase crop yield and decrease N loss, but its internal mechanisms have not been well studied, especially from the aspects of population dynamics and structure, ear fruiting traits, N absorption and utilization. Field experiments, with three N rates 120 (N1), 180 (N2) and 240 (N3) kg N ha-1 and three N topdressing ratios T1 (7:3), T2 (6:4) and T3 (5:5) were conducted. At the same N level, the N accumulation amount in leaf, grain and plant in T2 were higher than that in T3 and T1, and increasing 60 kg N ha-1 (N3 compared to N2, N2 compared to N1) significantly enhanced N accumulation amount . The effect of N topdressing ratio on partial factor productivity of applied N was consistently T2 > T3 > T1, but T1 was more conducive to improving N utilization efficiency for grain and biomass production. After jointing stage, compared to T1 and T3, T2 was more conductive to increasing the population growth rate of plant height, leaf area index, leaf area growth rate, dry matter weight, dry matter accumulation rate, light interception rate and spikelets of population, and the above-mentioned indexes of population could be significantly enhanced by increasing 120 kg N ha-1. T2 increased the fruiting spikelets per ear, grains per ear, grain weight per ear, fruiting rate per ear, grain filling rate per ear and yield, but decreased the sterile spikelets at the top and bottom and imperfect grains per ear. Increasing N from 120 kg ha-1 to 180 kg ha-1 or from 180 kg ha-1 to 240 kg ha-1 significantly enhanced yield. The N accumulation amount in grain, leaf and plant, leaf area growth rate, dry matter accumulation rate, light interception rate, population spikelets, fruiting spikelets per ear, grain filling rate and yield were significantly positively correlated with each other. Suitable N application rate with N topdressing ratio 6:4 would more effectively improve N efficiency, population dynamics and structure, ear fruiting traits and yield, but the effect of N topdressing ratio was not as significant as that of increasing 60 kg N ha-1.